Adsorção do corante reativo azul 5G utilizando escama de peixe como adsorvente - Ribeiro, Caroline (2014)
Textile industries remarkably present high consumption of water and elevated generation of wastewater. In most cases, these effluents are contaminated with a large amount of dyes, requiring previous treatment to disposal in the receiving bodies of water like rivers and lakes, or prior to its reutilization in the industry. The aim of this study was to evaluate the adsorption potential of tilapia (Oreochromis niloticus) scales of the reactive blue 5G dye and characterize this potential sorbent material, since it is an abundant waste of fish slaughterhouses of the western region of Paraná. For this purpose, characterization of the scale were carried out by OM, SEM, EDS, N2 physisorption, XRD, pHZPC, FTIR and FT-Raman. Experiments were performed in closed batch system to examine the effect of the particle diameter (6, 16, 32, 100, 150, 325 mesh and base), the adsorbent mass (0.1, 0.2 and 0.3 g), initial pH of the dye solution (2.0, 7.5 and 10.0) and the chemical pretreatment at the scales adsorption capacity. Finally, equilibrium assays were performed at the optimum conditions obtained. Further experiments were performed at fixed bed continuous system, the breakthrough curves were carried at different particle diameters (12, 16, 32 mesh and granulometric mixture) and under different pH values of the feed solution (2.0, 5.5, 7.5 and 10). Furthermore, the influence of treatment chemical adsorption was also studied. Moreover, the amount of dissolved organic carbon was measured during the adsorption process to examine the possibility of lixiviation. The material characterization indicated low incidence of pores on the scale surface, and the presence of chemical groups characteristic of collagen and hydroxyapatite. PHZPC analysis demonstrated that the point of zero charge of the scale was 7.64. At the both batch and column adsorption process higher values of adsorption capacity was reached by using the particle sizes 6, 16 and 32 mesh, at initial pH 2.0. The chemical treatment did not present any influence at the adsorbent adsorption capacity. Langmuir and Radke-Prausnitz isotherms best represented the equilibrium data of batch process. For the fixed bed process assays, the largest adsorption capacity was achieved by using the granulometric mixture of scales, at pH 2.0, at these conditions the highest adsorption capacity reached was q = 394.8 mg g-1, achieving a breakthrough time of tb = 20.5 h at the feed concentration of 75 mg L-1. The dissolved organic carbon amount increased during the experiment due to the dye solution concentration rise. Considering the high removal levels and the low cost of the material, tilapia scale present a potential use as alternative adsorbent.